Analisa Rasio Parkir Mobil untuk Kantor Swasta di Jakarta - Michael Tedja (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Jakarta's economy grew rapidly accompanied by the rapid growth of private office buildings in different areas of the city. This condition causes the need for car parking facilities at any existing private office buildings. Given the past 20 years, the Jakarta administration has never revised standard parking requirement in Jakarta. It causes the need be reviewed, to the extent appropriate parking ratio for a private office in the current period. This research is carried out on a number of park buildings at offices in Jakarta, the lower and upper limits of the implementation, then compared to the city standard parking. The results showed that the ratio standard park in Jakarta is no longer eligible based on the facts found.